Pelatihan Digital Financial Literacy Bagi UMKM Ikan Asap Desa Bulak, Kecamatan Rowosari, Kabupaten Kendal - Mutamimah Mutamimah; Lisa Kartikasari; Gunawan Gunawan; Indri Kartika (Forum Kerjasama Pendidikan Tinggi, 2022)
Smoked fish SMEs have a strategic role in economic empowerment and poverty reduction in Kab. Kendal. However, the smoked fish SMEs have not developed well, one of the reasons is that the majority of them do not have the knowledge, understanding and skills of digital finance. They use digital only through watshap, face book, IG to market smoked fish products to various regions. In addition, the MSMEs of smoked fish in Bulak Village do not understand the risks of using digital, and do not understand the method of digitally recording financial transactions. Therefore, the purpose of this community service is to increase knowledge, understanding, and digital financial skills through digital financial literacy for smoked fish MSMEs in Bulak Village, Kec. Rowosari, Kab. Kendal. The implementation method consists of 3 stages, namely: a). Conducted an initial survey to the location with the head of Bulak Village, smoked fish MSMEs players and the Kab. Kendal to find out the potential and problems of smoked fish MSMEs in Bulak Village, Kec. Rowosari, Kab. Kendal. b). Provide digital financial literacy training for smoked fish MSMEs in Bulak Village, Rowosari District, Kab. Kendal. c). Assessing the performance of community service. The results show that digital financial literacy training can increase knowledge, understanding and skills in conducting digital transactions, digital financial risks, digital bookkeeping, and digital financial reports as a basis for decision making for smoked fish MSMEs in Bulak Village, Rowosari District, Kab. Kendal.